Determination of the Relationship Between Urinary Albumin to Creatinine Ratio and the Severity of Liver Disease in Patient with Decompensated Cirrhosis of Liver (Sir Salimullah Medical College Journal, 2025)
Background: Decompensated cirrhosis of liver may lead to renal hypoperfusion and dysfunction that may be predicted by urinary albumin-to-creatinine ratio (UACR) and this UACR value may be one of the predictors of severity of liver disease. The aim of the  study was to determine  the relationship of urinary albumin creatinine ratio with severity of liver disease in patients with decompensated cirrhosis of liver. Methods: A cross-sectional observational study was carried out in the Department of Hepatology, Bangladesh Medical University (Former - BSMMU), Dhaka on 100 patients of decompensated cirrhosis of liver of different etiology.  Patients were divided into two groups as based on UACR ≤30mg/g (group 1) and UACR ≥30 mg/g (group 2). The groups were compared of cirrhosis related features, complications, CTP, (Child-Turcotte-Pugh) score and Model for end-stage liver disease (MELD)  score.  A receiver-operator characteristic curve was used for prediction of UACR with CTP class. Results: Male female ratio was 3:2. Sixty six (66%) patients had hepatitis B. Mean CP score 9.34±1.2, mean MELD score 20.6±6.96, mean urinary creatinine 81.5±78.0, urinary microalbumin 31.5±37.33 and mean UACR was 41.86±43.96. The difference was statistically significant (p